The Meanings of Zawj and Imraʾah in the Qurʾān: A Lexico-Statistical Analysis - Seyed Yousef Yasereh; Iman Kanani (Al-Bayan: Jurnal Studi Al-Qur'an dan Tafsir, 2025)
The Qurʾān’s deliberate selectivity in its lexical choices stands as one of its remarkable linguistic features. A detailed examination of individual words used in varied contexts is essential for an accurate interpretation of its meanings. This study focuses on two pivotal Qurʾānic terms: zawj and imra’ah. Despite their frequent appearance, comprehensive lexico-statistical analyses of these terms remain unexplored. This paper addresses this gap by (1) contextualising zawj and imra’ah within their Qurʾānic occurrences, (2) critically reviewing traditional and contemporary scholarly interpretations, (3) systematically cataloguing their morphological derivatives in both nominal and verbal forms, and (4) differentiating between their broad and specific semantic roles throughout the text. This multifaceted approach reveals subtle but significant semantic distinctions between zawj—often denoting pairs or companions—and imra’ah—primarily referring to women, particularly in individualised social and legal contexts—thus enriching our understanding of their nuanced usage in the Qurʾān.